Understanding unemployment from the perspective of youth with different abilities in Brunei Darussalam - Nurul Nabilah Haji Roslan (Abdul Hamid Abu Sulayman Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
Employment is an indispensable existence to every individual in the world today. However, youth with different abilities (YWDA) may not experience employment. With other competitive job seekers in the job market, the YWDA may face rivals who have more potential and advantages in occupying positions. With negative perceptions in the form of doubt, judgments and labels as barriers, YWDA may face less recognition to be included in the work force. The objectives of this research are to describe YWDA’s conceptualisation of employment, identify different types of barriers to employment for YWDA in Brunei and examine the role of parents in supporting YWDA’s employment. Two theoretical frameworks were chosen to explain the findings namely, the social model of disability which explains the barriers surrounding the PWDA leading to unemployment and the economic model of disability that focuses on the PWDA’s ability in employment. This study employed the qualitative method, particularly using unstructured interview to obtain relevant data. Fifteen YWDA were recruited using snowball sampling. The findings led to three themes: 1) Conceptualisation of Employment 2) Dimensions of Unemployment and 3) Readiness to Support YWDA. Based on the findings, getting employed is meaningful to the participants. The researcher found that the barriers had indeed caused them to be unemployed even though they may have education and working experience. The YWDA should be given employment opportunities in order to erase the stereotypes. Thus, both the YWDA and the general society hold the responsibility in unfolding the connections to barriers.